Assessing Nurse Educator Student Informatics Competencies. - Anne Bove, Lisa; Sauer, Penny (Online Journal of Nursing Informatics, 2022)
Informatics is essential to nursing practice. The nurse educator student must be proficient at informatics to prepare students to enter the profession. Purpose: This study examined nurse educator students' informatics knowledge using the SANICS instrument. Methods: Participants enrolled in a graduate-level nurse educator course on informatics were surveyed using the SANICS instrument. The Institutional Review Board determined the study was exempt and survey results were anonymous. Results: There were 152 participants, with 94.1% (N=-143) females and 57.2% (N=87) less than 40 years old. Participant years of experience was well distributed with 35.1% (N=53) having 0-5 years; 26.5% (N=40) 6-10 years, and 38.4% (N=58) more than 10 years of experience. Participants scored near the proficient level of SANICS basic computer knowledge (M= 2.9), above the proficient level for SANICS role subscale (M= 3.22), and at the competent level for SANICS applied computer skills (M=2.42). Age and years of experience had a strong association (c2 (2) = 57.022, p<.001), with 31.3% of those who are older having 10 or more years of experience. Significance: Informatics needs to be taught and developed throughout all levels of nursing education. Nurse educator students should be at the proficient or expert level to teach the next generation of nurses. Today's healthcare system is constantly advancing with nurses using more technology to care for patients than ever before. This requires nurses to be proficient with informatics and information management. Education about how to use informatics to perform patient care begins in prelicensure education and continues in advanced degree programs. Various definitions of informatics exist, however, and no one tool assesses all the skills needed. The purpose of this article is to describe graduate nurse educator (NE) students' level of informatics competency.